A new multi-control-point pushover methodology for the seismic assessment of historic masonry buildings - Olivito, Renato Sante; Porzio, Saverio (Journal of Building Engineering, 2019)
Various methods are currently used for the seismic assessment of historic masonry buildings. Among the static approaches, definition of the capacity curve in pushover analysis is influenced by choice of the control point. However, masonry constructions are typically vulnerable to out-of-plane loads, and the control point might be located on structural elements subject to collapse mechanisms. The present work is aimed at developing a coupled numerical-geometrical methodology to represent the results arising from pushover analysis, by considering an appropriate number of Boundary Control Points (BCPs) that envelop the shape of the investigated structure. The proposed approach is verified by performing numerical simulations on the San Fili Castle of Stignano, located in the Calabria Region, in the south of Italy. The analyses, both static and dynamic, are developed in a nonlinear framework in which the behavior of the structure under seismic loads has been investigated. Further studies, taking into account the kinematic theorem of limit analysis, are performed on a significant failure mechanism in order to validate the results obtained. Spectral acceleration values are compared for all approaches. The results show detailed information about the global structural behavior of the building and its seismic safety. •A specific case study is chosen to develop a new way to detect out-of-plane mechanisms in historic masonry buildings.•A numerical-geometrical methodology to represent pushover curves is presented, by using proper boundary control points.•A sensitivity analysis is carried out to set the elastic springs that simulate secondary structural elements.•A graphical representation of damage is developed through spheres proportional to the displacements of each control point.•Further studies taking into account nonlinear dynamic and limit analyses are performed to compare spectral accelerations.